Cochrane Database of Systematic Reviews 2007
DOI: 10.1002/14651858.cd006801
|View full text |Cite
|
Sign up to set email alerts
|

Custom-made foot orthoses for the treatment of foot pain

Abstract: Analysis 1.2. Comparison 1 Custom-made foot orthoses versus sham orthoses for painful cavus feet, Outcome 2 Function. Analysis 1.3. Comparison 1 Custom-made foot orthoses versus sham orthoses for painful cavus feet, Outcome 3 Healthrelated quality of life. .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
0
8

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(87 citation statements)
references
References 32 publications
4
75
0
8
Order By: Relevance
“…The prefabricated orthoses have shown positive results in shortterm period, with a relative improvement in pain and function [8]. However, there is no evidence that rely on the use of prefabricated and customized orthoses for the long-term period, longer one year [13].…”
Section: Orthosesmentioning
confidence: 99%
“…The prefabricated orthoses have shown positive results in shortterm period, with a relative improvement in pain and function [8]. However, there is no evidence that rely on the use of prefabricated and customized orthoses for the long-term period, longer one year [13].…”
Section: Orthosesmentioning
confidence: 99%
“…53 A Cochrane review in 1999 declared that 'the use of shock absorbing inserts in footwear probably reduces the incidence of stress fractures in military personnel' (A). 54 Another Cochrane review found evidence that custom--made orthoses for feet were effective in the treatment of cavus foot pain (A). 55 Running shoes with neutral insoles have recently demonstrated a statistically significant reduction in plantar pressure in athletes with cavus feet (A).…”
Section: What Are the Indications For Surgical Treatment?mentioning
confidence: 99%
“…Después de 6 meses, 362 pacientes cumplen criterios de AR. La incidencia anual estimada de EA fue de 25/100000 habitantes (IC del 95%: 23,26). La incidencia anual de la AR fue de 8.3 casos por 100 000 (IC del 95%: 7,5, 9,2): 11.3/100 000 en mujeres (IC del 95%: 10,0, 12,8), y 5.2/100 000 en hombres (IC del 95%: 4,3 , 6,3).…”
Section: Introductionunclassified